Bioinspired Surfaces With Switchable Wettability - Han, Dong-Dong; Cai, Qing; Chen, Zhao-Di; Li, Ji-Chao; Mao, Jiang-Wei; Lv, Pin; Gao, Bing-Rong (Frontiers in Chemistry, 2020)
The surface wettability of plants exhibits many unique advantages, which enhances the environmental adaptability of plants. In view of the rapid development of responsive materials, smart surfaces have been explored extensively to regulate surface wettability through external stimuli. Herein, we summarized recent advancements in bioinspired surfaces with switchable wettability. Typical bioinspired surfaces with switchable wettability and their emerging applications have been reviewed. In the end, we have discussed the remaining challenges and provided perspective on future development.